2015 IEEE/ACM 37th IEEE International Conference on Software Engineering 2015
DOI: 10.1109/icse.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

How Much Up-Front? A Grounded theory of Agile Architecture

Abstract: The tension between software architecture and agility is not well understood by agile practitioners or researchers. If an agile software team spends too little time designing architecture up-front then the team faces increased risk and higher chance of failure; if the team spends too much time the delivery of value to the customer is delayed, and responding to change can become extremely difficult. This paper presents a grounded theory of agile architecture that describes how agile software teams answer the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Finally, as the EnviDat development workflow will gradually shift to Agile software development principles (Beck et al, 2001), this change will impact the EnviDat System Architecture. Consequently, a continuous architectural redesign of the EnviDat system architecture is necessary in order to support the proper application of the Continuous Delivery (Beck et al, 2001) concept through an agile architecture that, according to (Waterman et al, 2015) "is being able to be easily modified in response to changing requirements, is tolerant of change, and is incrementally and iteratively designed -the product of an agile development process".…”
Section: Envidat System Architecture and Technology Stackmentioning
confidence: 99%
“…Finally, as the EnviDat development workflow will gradually shift to Agile software development principles (Beck et al, 2001), this change will impact the EnviDat System Architecture. Consequently, a continuous architectural redesign of the EnviDat system architecture is necessary in order to support the proper application of the Continuous Delivery (Beck et al, 2001) concept through an agile architecture that, according to (Waterman et al, 2015) "is being able to be easily modified in response to changing requirements, is tolerant of change, and is incrementally and iteratively designed -the product of an agile development process".…”
Section: Envidat System Architecture and Technology Stackmentioning
confidence: 99%
“…A close work is Rothenberger and Srite's investigation, combining grounded theory and case studies, on the factors that influence the degree of customisation on ERP systems [5]. More generally, researchers used the grounded theory method to investigate how an agile development team control the quality [6], how much architecting is proper for different agile teams [7], etc. More approaches can be found in a survey by Stol et al [3].…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have also looked at social factors that influence architecture. For example, Waterman et al [57] interviewed agile software developers to determine how much architectural design to conduct "up-front" as opposed to allowing it to emerge during development. The authors identified five different strategies-respond to change, address risk, emergent architecture, big design up-front, frameworks and template architectures-that can help an agile developer make this decision.…”
Section: Related Workmentioning
confidence: 99%